Contemporary Solutions for Advanced Catalytic Materials with a High Impact on Society - Coman, Simona M.; Tudorache, Madalina; Jacobsen, Elisabeth Egholm (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The main aim of this reprint is to highlight the contributions of advanced catalytic materials in the evolution of contemporary society, delivering practical and useful solutions with a positive societal, economic, and environmental impact.